What makes poor countries poor? institutional determinants of development - Trebilcock, Michael J. (Edward Elgar CheltenhamGB, 2011)
Focuses on the idea that institutions in general and legal institutions in particular matter for development. Offers insights into how lawyers and institution builders can best employ their skills to address some of the challenges of institutional reform.